Nanocatalyst: A Brief Review on Synthesis to Applications - Somwanshi, Saurabh B.; Somvanshi, Sandeep B.; Kharat, Prashant B. (Journal of physics. Conference series, 2020)
As the world is at present confronting tremendous issues concerning the atmosphere, energy, and the environment, catalysis innovations have all the earmarks of being getting critical to energy, synthesis process, and environmental areas. In the recent years, transformation of the research on catalytic activities and advanced catalyst was seen with the advancement of nanotechnology. Undoubtedly, the utilization of nanomaterials in catalysis and, all the more especially, inorganic nanoparticles has pulled in many research attempts over the globe to create imaginative and greener conventions. These nanoparticles can be used as the catalyst or as mediator and can encourage the reactant procedure in new medium such as, water. Besides, attributable to their little size and expanded surface area, nano-catalysts have obviously risen as offering an interesting candidate at the interface among homogeneous and heterogeneous catalysis, taking into consideration an expanded response rate. Furthermore, nanoparticles give extra reactant functionalities because of their interesting inherent properties (e.g., nanomagnetism, photocatalytic activity). Along these lines, in this pursuit for eco-friendly and more affordable catalyst, nano-catalysis is turning into a significant field in science, which is applied broadly in the academics and industrial areas. This brief review principally centered around portraying the major comprehension of nano-catalysis, how remarkable catalytic property and other explicit properties of nanomaterials rely upon its size and structure at the nano level.